2015
DOI: 10.1007/s13361-015-1309-5
|View full text |Cite
|
Sign up to set email alerts
|

Inductively Coupled Plasma Zoom–Time-of-Flight Mass Spectrometry

Abstract: Abstract. A zoom-time-of-flight mass spectrometer has been coupled to an inductively coupled plasma (ICP) ionization source. Zoom-time-of-flight mass spectrometry (zoom-TOFMS) combines two complementary types of velocity-based mass separation. Specifically, zoom-TOFMS alternates between conventional, constantenergy acceleration (CEA) TOFMS and energy-focused, constant-momentum acceleration (CMA) (zoom) TOFMS. The CMA mode provides a mass-resolution enhancement of 1.5-1.7× over CEA-TOFMS in the current, 35-cm I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…At a repetition rate of 10 kHz, for example, S/N for 63 Cu + under CEA‐TOFMS was 990, while at an enhanced repetition rate of 30 kHz in CMA‐TOFMS, S/N was increased to 10,000. The authors also demonstrated the utility of the zoom‐TOFMS technique for ICP‐MS (Dennis et al, 2016c). Detection limits for a range of elements were decreased by approximately 40‐times (2.1 ppt in CEA‐TOFMS to 0.054 ppt in CMA‐TOFMS), on average, when using CMA‐TOFMS as compared to conventional ICP‐TOFMS (e.g., 155 Gd + CMA‐TOFMS = 0.033 ppt).…”
Section: Constant Momentum Acceleration (Cma) Tofmsmentioning
confidence: 99%
“…At a repetition rate of 10 kHz, for example, S/N for 63 Cu + under CEA‐TOFMS was 990, while at an enhanced repetition rate of 30 kHz in CMA‐TOFMS, S/N was increased to 10,000. The authors also demonstrated the utility of the zoom‐TOFMS technique for ICP‐MS (Dennis et al, 2016c). Detection limits for a range of elements were decreased by approximately 40‐times (2.1 ppt in CEA‐TOFMS to 0.054 ppt in CMA‐TOFMS), on average, when using CMA‐TOFMS as compared to conventional ICP‐TOFMS (e.g., 155 Gd + CMA‐TOFMS = 0.033 ppt).…”
Section: Constant Momentum Acceleration (Cma) Tofmsmentioning
confidence: 99%